Realism/anti-realism in 20th-century literature - Baron, Christine, 1960-; Engel, Manfred, 1953- (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2010)
Modernist literature and art have been dominated by a disinterest in mere empirical and social reality and a discontent with habitualized perception and the world-view of convention, reason, and pragmatism. This anti-realistic attitude originated in the e.